1992
DOI: 10.1111/j.1365-3083.1992.tb02938.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Mycobacterial 30‐kDa Region Proteins with the Cutaneous Infiltrates of Leprosy Lesions

Abstract: The granulomatous skin lesions of human leprosy are known to be due to the cutaneous immune reaction to various mycobacterial antigens. In the present study, by immunohistochemical analysis using a previously characterized monoclonal antibody (MoAb) 3A8 we have demonstrated a selective expression of the 3A8 epitope of mycobacterial 30-kDa proteins, the major secreted proteins of mycobacteria, in various forms of leprosy lesions across the clinical spectrum. The localization of MoAb 3A8 staining is confined to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…The 85B proteins are important immunogenic components of the cell walls of M. tuberculosis (4) and, consequently, may persist at the sites of infection. Rambukkana and colleagues have demonstrated the presence of M leprae 85B protein both in the cell walls of the bacillus and as an extracellular protein in the cutaneous lesions of leprosy patients (25,26). The current study confirms that the recombinant 85B protein of M bovis, MPB59, which is almost identical to its M tuberculosis counterpart, is an important T-cell antigen, being recognized by more than 95% of BCG vaccinees and half of TB patients.…”
Section: Discussionsupporting
confidence: 80%
“…The 85B proteins are important immunogenic components of the cell walls of M. tuberculosis (4) and, consequently, may persist at the sites of infection. Rambukkana and colleagues have demonstrated the presence of M leprae 85B protein both in the cell walls of the bacillus and as an extracellular protein in the cutaneous lesions of leprosy patients (25,26). The current study confirms that the recombinant 85B protein of M bovis, MPB59, which is almost identical to its M tuberculosis counterpart, is an important T-cell antigen, being recognized by more than 95% of BCG vaccinees and half of TB patients.…”
Section: Discussionsupporting
confidence: 80%
“…Shetty et al 11 have also found that antigen staining within nerves occurs predominantly in macrophages and epithelioid cells. The noncellular diffuse infiltrate associated staining pattern we observed has also been reported by Rambukkana et al, 12 who noted this type of staining in a skin biopsy from a multibacillary patient with a type I reaction. The strength of staining seen in these biopsies suggests that there is a relative abundance of antigen in type I reactions; staining is much stronger than in new paucibacillary patients and all types of treated patient.…”
Section: Discussionsupporting
confidence: 66%
“…In fact, monocyte agglutination activity of human T-cell FN has been shown to be significantly inhibited by α-Ag in itro [38]. It was reported that the production of α-Ag is increased at tissue sites where mycobacteria grow [39]. α-Ag might therefore be expected to modify the local effective response of host lymphocytes against infected mycobacteria.…”
Section: Discussionmentioning
confidence: 99%